The Regional Western Sweden SOM Survey 1994 - SOM Institute, University of Gothenburg (University of Gothenburg, 1995)
This is the third study in the series of SOM-surveys carried out in Western Sweden exclusively. The questionnaire was divided into six subject fields: mass media; politics and society; the municipality of Göteborg; traffic and environment; leisure and housing; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New questions in the 1994 survey dealt with efforts to influence or change activities on local or county level; interest in environmental issues; access to and use of the 'Environmental catalogue'; opinions on environmental issues local government ought to work on, and to what extent the respondent was prepared to contribute personally to a better environment; establishments and places visited during the last year; favourite soccer team; method of travel to work/school; and vote in the general election and in the local election in 1994. Respondents living in Göteborg were asked about public transport costs, they also had to place the local parties and a number of local politicians on a scale ranging from strongly dislike to strongly like, and they had to state which characteristics suited the local politicians Göran Johansson (socialdem.) and Johnny Magnusson (cons.).

Purpose:

Study attitudes and behaviours that are linked to local and regional issues and phenomena

Detta är den tredje studien i serien SOM-undersökningar genomförda i Västsverige. Undersökningens frågeformulär var indelat i sex områden: massmedia; politik och samhälle; Göteborgs kommun; trafik och miljö; fritid och boende; samt bakgrundsfrågor. Huvuddelen av enkätens frågor återfinns även i en eller flera av de tidigare undersökningarna. Nya frågeställningar i 1994 års undersökning tar upp försök att påverka eller förändra kommunal eller landstingskommunal verksamhet, intresse för miljöfrågor, tillgång till och utnyttjande av Miljökatalogen, inställning till vilka miljöfrågor kommunen bör arbeta med och i vilken utsträckning man personligen är beredd att bidra till en bättre miljö. Därutöver ställdes frågor om vilka anläggningar och utflyktsmål man besökt under senaste året, favoritlag i fotboll, vilket färdsätt man senast använde sig av för att ta sig till arbetet/skolan, samt hur man röstat i riksdags- och kommunfullmäktigevalet 1994. Respondenter bosatta i Göteborgs kommun fick frågor om kostnader för kollektivtrafiken, dessutom fick de placera de lokala partierna och ett antal kommunala politiker på en skala som sträckte sig från ogillar starkt till gillar starkt, samt ange vilka egenskaper de ansåg passade in på de lokala politikerna Göran Johansson (s) och Johnny Magnusson (m).

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 1994
Väst-SOM 1994
Keywords: internal politics; inrikespolitik; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap